2001
DOI: 10.1111/j.1469-7793.2001.t01-1-00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a biological dawn and dusk in the human circadian timing system

Abstract: Because individuals differ in the phase angle at which their circadian rhythms are entrained to external time cues, averaging group data relative to clock time sometimes obscures abrupt changes that are characteristic of waveforms of the rhythms in individuals. Such changes may have important implications for the temporal organization of human circadian physiology. To control for variance in phase angle of entrainment, we used dual internal reference points ‐ onset and offset of the nocturnal period of melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 38 publications
2
89
0
Order By: Relevance
“…Further both are affected by bright light (Scheer & Buijs, 1999;Thorn et al, 2004;Claustrat et al, 2005;Wehr et al, 2001). Despite these complementary mechanisms and functions data from this study suggest no direct relationship between the hormones in the post awakening period; relationships later in the day were not explored.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Further both are affected by bright light (Scheer & Buijs, 1999;Thorn et al, 2004;Claustrat et al, 2005;Wehr et al, 2001). Despite these complementary mechanisms and functions data from this study suggest no direct relationship between the hormones in the post awakening period; relationships later in the day were not explored.…”
Section: Discussionmentioning
confidence: 65%
“…Circadian rhythms exhibit distinct diurnal and nocturnal states with an abrupt switch-like transition between sleep and waking; initiating a more gradual change in function to prepare for the day ahead: biological dawn (Morris et al, 2012;Wehr et al, 2001). Biological dawn is frequently measured by examination of post-awakening cortisol secretion, an index of circadian functioning of the HPA axis.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating levels of both display robust diurnal patterns (Migeon et al 1956, Ralph et al 1971. Using the CR and FD experimental protocols, the secretion rhythms of cortisol (el-Hajj Fuleihan et al 1997, Wehr et al 2001, Aeschbach et al 2003, Scheer et al 2010) and melatonin (Dijk et al 1999, Wehr et al 2001, Cain et al 2010, Gooley et al 2011 have been shown to be under direct regulation by the circadian clock. Not surprisingly, both hormones also act as major hormonal output pathways that propagate the time signal from the SCN to various other tissues.…”
Section: Endocrine Rhythms: Clock Vs Behavioral Regulationmentioning
confidence: 99%
“…A possible shift in the offset of the melatonin rhythm or suppression in the early morning was not measured. It could be hypothesized that morning light induces a larger phase advance in the offset than in the onset of the melatonin rhythm (Illnerová & Sumová, 1997;Warman et al, 2003;Wehr et al, 2001). This effect, however, is thought to be transient and only present during the first days after morning light.…”
Section: Effects Of Artificial Dawn On Sleep Inertia 1233mentioning
confidence: 99%